Ground-based passive generation of Solar Particle Event spectra: Planning and manufacturing of a 3D-printed modulator - Tabea Pfuhl; Uli Weber; Felix Horst; Marco Durante; Christoph Schuy (Zeitschrift für Medizinische Physik, 2024)
The generation of space radiation on Earth is essential to study and predict the effects of radiation on space travelers, electronics, or materials during future long-term space missions. Next to the heavy ions of the galactic cosmic rays, solar particle events play a major role concerning the radiation risk in space, which consist of intermediate-energy protons with broad spectra and energies up to a few hundred MeV. This work describes an approach for the ground-based generation of solar particle events. As a proof of principle, a passive beam modulator with a specific funnel-shaped periodic structure was designed and is used to convert a monoenergetic proton beam into a spectral proton energy distribution, mimicking a solar particle event from August 1972, which is known as one of the strongest recorded SPE events. The required proton beam of 220 MeV can be generated at many existing particle accelerators at research or particle therapy facilities. The planning, manufacturing and testing of the modulator is described step by step. Its correct manufacturing and the characteristics of the solar particle event simulator are tested experimentally and by means of Monte Carlo simulations. Future modulators will follow the same concept with minor adjustments such as a larger lateral extension. As of now, the presented beam modulator is available to the research community to conduct experiments at GSI for exposure under solar particle event conditions. In addition, researchers can use and apply the described concept to design and print their individualized modulator to reproduce any desired solar particle event spectrum or request the presented modulator geometry from the authors.